Pentingnya Pendidikan Pancasila Dalam Membangun Kesadaran Identitas Nasional Dan Semangat Cinta Tanah Air Pada Mahasiswa - Fajar Ramdani; Muhammad Nasyih Ulwan; Larasati Azzahra Arief; Muhamad Fattan Al-Farisi; Rifki Rochiman; R. Muhammad Nadzriel Nuryaddin H; Arnold Kogoya; Yayang Furi Furnamasari (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
Education is a complex process that involves knowledge transfer, character development and philosophical values. Pancasila and Citizenship Education is very important to shape the character of the young generation, especially students, in Indonesia. To develop solidarity and nationalism, understanding national identity is important, especially for the younger generation who act as agents of change in the era of globalization. This study aims to explore the role of Pancasila and Citizenship education in shaping the character of university students as agents of change and guardians of national values amid the influence of globalization. This study collects, reviews and analyzes various literatures, including books, scientific articles, journals and relevant documents. As agents of change, political controllers, and guardians of national values, students play an important role in Indonesia's progress. Citizenship education is still needed to form a young generation that has a national spirit, loves the country, and actively participates in nation building. Pancasila education is essential to build awareness of national identity and a spirit of patriotism in the younger generation. Students act as drivers of change who defend the nation's values and support state integration. Civic education helps build a strong, knowledgeable and committed national character. This education is not only part of the academic curriculum, but also a commitment to forming a responsible generation that has high civic awareness.